The Nematode Caenorhabditis elegans, Stress and Aging: Identifying the Complex Interplay of Genetic Pathways Following the Treatment with Humic Substances - Menzel, Ralph; Menzel, Stefanie; Swain, Suresh C.; Pietsch, Kerstin; Tiedt, Sophie; Witczak, Jördis; Sturzenbaum, Stephen R.; Steinberg, Christian E. (Frontiers in Genetics, 2012)
Low concentrations of the dissolved leonardite humic acid HuminFeed® (HF) prolonged the lifespan and enhanced the thermal stress resistance of the model organism Caenorhabditis elegans. However, growth was impaired and reproduction delayed, effects which have also been identified in response to other polyphenolic monomers, including Tannic acid, Rosmarinic acid, and Caffeic acid. Moreover, a chemical modification of HF, which increases its phenolic/quinonoid moieties, magnified the biological impact on C. elegans. To gain a deep insight into the molecular basis of these effects, we performed global transcriptomics on young adult (3 d) and old adult (11 d) nematodes exposed to two different concentrations of HF. We also studied several C. elegans mutant strains in respect to HF derived longevity and compared all results with data obtained for the chemically modified HF. The gene expression pattern of young HF treated nematodes displayed a significant overlap to other conditions known to provoke longevity, including various plant polyphenol monomers. Besides the regulation of parts of the metabolism, TGF- signaling and Insulin-like signaling, lysosomal activities seem to contribute most to HF’s and modified HF’s lifespan prolonging action. These results support the notion that the phenolic/quinonoid moieties of humic substances are major building blocks that drive the physiological effects observed in C. elegans.